Pengaruh perceived organizational support dan intrinsic motivation terhadap organizational citizenship behavior melalui organizational commitment sebagai variabel mediasi - Ika Tantri Fatmasari; Khoirur Rozaq (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2023)
This study examines and analyses the effect of perceived organizational support and intrinsic motivation on organizational citizenship behavior with the mediating role of organizational commitment to employees of PT. X. Quantitative method was used in this study. The population and sample of the study are 66 partner employees using a sampling technique, namely the saturated sample technique. The statistical analysis of this research is PLS with SmartPLS 4.0 software. The results of this study indicate that perceived organizational support does not affect organizational citizenship behavior. Perceived organizational support has a positive and significant effect on organizational commitment. Intrinsic motivation has a positive and significant effect on organizational commitment. Intrinsic motivation has a positive and significant effect on organizational citizenship behavior. Organizational commitment has a positive and significant effect on organizational citizenship behavior. Organizational commitment as an intervening variable cannot influence the relationship between perceived organizational support on organizational citizenship behavior. Organizational commitment as an intervening variable does not mediate the relationship between intrinsic motivation on organizational citizenship behavior at PT. X. The implications based on the research results show that companies must pay attention to the work targets given because they can impact OCB.